Napisz w najprostszej postaci :

1.)-(2a-2b-3)-(-3a+2b+3) =
2.)(3x-7)-(-2x+1)+(-5x+4) =
3.)-(7a-2b+4)+(-3a+2b-5) =
4.)(-10x(2)+4x-1)-2x(2)-3x-3) =
5.)(8a-2b+3)-(3a+2b-4) =
6.)-(a+b)-(-a-b)+(-a-b) =
7.)(3x+5y-6)-(-2x+3y+7)-(3x+y-1) =
8.) ------------------------------------
9.)(5x(2)-3x+7)-(2x-x(2)+4) =
10.)-(4a+2b-3)+(-a-b-a) =

Ps.To Jednomiany . (2) oznacza do potęgi drógiej .

2

Odpowiedzi

2010-02-20T16:45:44+01:00
1.)-(2a-2b-3)-(-3a+2b+3) =-2a+2b+3+3a-2b-3=5a
2.)(3x-7)-(-2x+1)+(-5x+4) =3x-7+2x-1-5x+4=-4
3.)-(7a-2b+4)+(-3a+2b-5) =-7a+2b-4-3a+2b-5=-10a+4b-9
4.)(-10x²+4x-1)-(2x²-3x-3) =-10x²+4x-1-2x²+3x+3=8x²+7x+2
5.)(8a-2b+3)-(3a+2b-4) =8a-2b+3-3a-2b+4=5a-4b+7
6.)-(a+b)-(-a-b)+(-a-b) =-a-b+a+b-a-b=a-b
7.)(3x+5y-6)-(-2x+3y+7)-(3x+y-1) =
3x+5y-6+2x-3y-7-3x-y+1=2x+y+1

9.)(5x²-3x+7)-(2x-x²+4) =
5x²-3x+7-2x+x²-4=6x²-5x+3
10.)-(4a+2b-3)+(-a-b-a) =-4a-2b+3-a-b-a=-6a-3b+3

proszę ;-)
Najlepsza Odpowiedź!
2010-02-20T16:47:12+01:00
1.)
-(2a-2b-3)-(-3a+2b+3) =
-2a+2b+3+3a-2b-3=a

2.)
(3x-7)-(-2x+1)+(-5x+4) =
3x-7+2x-1-5x+4= -4

3.)
-(7a-2b+4)+(-3a+2b-5) =
-7a+2b-4-3a+2b-5=
-10a+4b-9
4.)
(-10x(2)+4x-1)-2x(2)-3x-3) =
-10x(2)+4x-1-2x(2)-3x-3=
-12x(2)+x-4

5.)
(8a-2b+3)-(3a+2b-4) =
8a-2b+3-3a-2b+4=
5a-4b+7
6.)
-(a+b)-(-a-b)+(-a-b) =
-a-b+a+b-a-b= -a-b
7.)
(3x+5y-6)-(-2x+3y+7)-(3x+y-1) =
3x+5y-6+2x-3y-7-3x-y+1=
5x+y-12
8.) ------------------------------------
9.)
(5x(2)-3x+7)-(2x-x(2)+4) =
5x(2)-3x+7-2x+x(2)-4=
6x(2)-5x+3
10.)
-(4a+2b-3)+(-a-b-a) =
-4a-2b+3-a-b-a=
-6a-3b+3